Spectral Distribution Method Calculations Of Nuclear Level Densities - Gharghar, Fawzeya (المجلة العلمية لكلية التربية, 2023)
The spectral distribution method offers an attractive framework in the study of nuclear level density with inclusion of the two-body force. We present a global parametrization of nuclear level densities taking into consideration the shell-model structures and residual interactions. The noninteracting and interacting particles parts of the Hamiltonian can be studied separately and then the results convoluted to calculate the total level density. The distribution for such a Hamiltonian shows that Gaussian distribution is a good approximation for the level density formalism.